Comparison of Umbilical Cord and Postnatal Fourth Month Serum 25-OH Vitamin D Levels of Late Preterm and Term Infants - Dilek Yavuzcan Öztürk; Seçil Erçin; Ayşem Kaya; Güner Karatekin (Cam & Sakura Medical Journal, 2022)
Objective: Our aim was to compare vitamin D levels of late preterm and term babies measured at birth and at postnatal 4th month. Material and Methods: One hundred four late preterm infants (group I) and 118 term infants (group II) were enrolled in the study. Maternal age, parity, morbidities related to pregnancy, educational status, sun exposure, dressing style and use of multivitamin supplements were recorded. Gestational age, birth weight, height, head circumference, sex of infants were also recorded. Umbilical cord blood was collected from all participants and cord blood 25-OH vitamin D levels were measured. Oral vitamin D 3 supplementation (400 IU) was started on postnatal 15th day for all babies. Vitamin D measurements were repeated at the postnatal fourth month. Serum 25-OH vitamin D concentrations were measured by chemiluminescence assay. The results were evaluated statistically. Results: Mean umbilical cord 25-OH vitamin D levels of groups I and II were 7.6+-6.6 ng/mL and 7.5+-6.5 ng/mL, respectively (p=0.835). Eighty-four percent of infants in group I and 78% of infants in group II had severe vitamin D deficiency (<10 ng/mL). Cord blood vitamin D levels in both groups did not differ in terms of sun exposure (p=0.595). A statistically significant increase in 25-OH vitamin D levels was seen after vitamin D supplementation in both groups (p<0.05). Also, 25-OH vitamin D levels at postnatal 4th month of life between the two groups did not differ (group I 34.4+-8.7 ng/mL vs. group II 38.9+-12.7 ng/mL; p=0.306). Conclusion: Although the umbilical cord 25-OH vitamin D blood levels of late preterm infants were similar to term infants', a high incidence of vitamin D deficiency in the umbilical cord blood was observed in both groups. Late prematurity did not pose an additional risk factor for vitamin D deficiency. After four months of oral replacement therapy, repeated serum vitamin D-level measurement confirmed significantly increased vitamin levels, almost reaching normal values.